Protocol to infer and analyze miRNA sponge modules in heterogeneous data using miRSM 2.0 - Junpeng Zhang; Xuemei Wei; Chunwen Zhao; Haolin Yang (STAR Protocols, 2024)
Summary: MicroRNA (miRNA) sponges synergistically modulate physiological and pathological processes in the form of modules or clusters. Here, we present a protocol for inferring and analyzing miRNA sponge modules in heterogeneous data using the R package miRSM 2.0. We describe steps for identifying gene modules, inferring miRNA sponge modules at multi-sample and single-sample levels, and performing modular analysis. From the perspective of computational biology, miRSM 2.0 has the potential to advance our understanding of the role of miRNA sponges in diseases.For complete details on the use and execution of this protocol, please refer to Zhang et al.1,2,3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.